2017
DOI: 10.1186/s12974-017-0808-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of BCG vaccination and enriched environment promote neurogenesis and spatial cognition via a shift in meningeal macrophage M2 polarization

Abstract: BackgroundThe spatial learning abilities of developing mice benefit from extrinsic cues, such as an enriched environment, with concomitant enhancement in cognitive functions. Interestingly, such enhancements can be further increased through intrinsic Bacillus Calmette-Guérin (BCG) vaccination.ResultsHere, we first report that combined neonatal BCG vaccination and exposure to an enriched environment (Enr) induced combined neurobeneficial effects, including hippocampal long-term potentiation, and increased neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…The mechanisms by which CD8 + T cells are affecting plasticity are also unknown. Since there is no direct physical contact between T cells and neurons in the brain parenchyma, the intercellular dialogue mediated by soluble molecules may involve cellular intermediates, which could be perivascular or meningeal macrophages, microglia, and/or astrocytes (Qi et al, 2017). We have obtained interesting data suggesting that in EE mice, astrocytes may serve as intermediates in the cascade linking EE-CD8 + T cells to neuronal plasticity in hippocampus (Suppl Fig 11).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanisms by which CD8 + T cells are affecting plasticity are also unknown. Since there is no direct physical contact between T cells and neurons in the brain parenchyma, the intercellular dialogue mediated by soluble molecules may involve cellular intermediates, which could be perivascular or meningeal macrophages, microglia, and/or astrocytes (Qi et al, 2017). We have obtained interesting data suggesting that in EE mice, astrocytes may serve as intermediates in the cascade linking EE-CD8 + T cells to neuronal plasticity in hippocampus (Suppl Fig 11).…”
Section: Discussionmentioning
confidence: 92%
“…Various cytokines have been shown to participate in the recruitment of T cells from the periphery (Qi et al, 2017). One can hypothesize that the changes observed in CD8 + T cells from the choroid plexus of EE vs.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, it was reported that neonatal BCG vaccination at a dose of 10 5 CFU elevated neurogenesis, synaptic plasticity, cognitive function, and the levels of neurotrophic factors in mice housed in a standard environment. 48 The forced swimming test (FST) is a behavioral despair test useful for probing the pathological mechanism of depression and for the evaluation of antidepressant drugs. 49 Antidepressants achieved their effects by reducing immobility time and increase or prolong active escape behaviors.…”
Section: G L I G L I G + a E L I G + A E L I G + A E L I G + B C G mentioning
confidence: 99%
“…They can produce neurotrophic factors that promote neuron progenitor proliferation, the migration of neuroblast cells and maturation of the newly born neurons . Therefore, the special macrophage M2 phenotype is becoming recognized as an important promotor of post–stroke brain repair …”
Section: The Role Of Neuroinflammation In Multiple Brain Repair Mechamentioning
confidence: 99%